ANALISIS PERGERAKAN PENDUDUK USIA KERJA DI KECAMATAN PEDURUNGAN SEBAGAI KAWASAN URBAN FRINGE KOTA SEMARANG (Studi Kasus Di Kelurahan Tlogosari Kulon) - Octavian Ady Jaya, Yopy; Hendarto, Mulyo (Diponegoro Journal of Economics, 2013)
This research investigates how do labor’s movement patterns in the Tlogosari Kulon area, sub-district of Pedurungan as urban fringe’s Semarang. The objectives in this research were: (1) identify the distribution of employment Pedurungan Sub-District residents, (2) identify the modes used to travel to work, (3) Identify the reasons to use these modes to travel to work, (4) identify the time away from home and time to go home, (5) identify the travel time to the place to work, (6) identify the costs incurred for transportation costs in a month. The existence of the problem of population growth and the convergence of land and transportation problems are problems that occur in different cities. Urban population has grown rapidly, there is also a linear increase in the number of vehicles. The phenomenon affects the increasing mobility of people and changes movement patterns that will lead to increased movement.